Posted by **Anonymous** on Sunday, April 21, 2013 at 11:12pm.

Simplify.

1. (1/log base 3 of 60)+ (1/log base 4 of 60)+ (1/log base 5 of 60)

2. (log base 16 of x)+ ( log base 4 of x) + (log base 2 of x)=7

- Algebra 2 .. -
**Steve**, Monday, April 22, 2013 at 12:26am
1/log_a(b) = log_b(a), so what you have is

log_60(3) + log_60(4) + log_60(5)

= log_60(3*4*5)

= log_60(60)

= 1

since 16=2^4=4^2, you have

log_16(x) + 2log_16(x) + 4log_16(x) = 7

7log_16(x) = 7

log_16(x) = 1

x=16

- Algebra 2 .. -
**Anonymous**, Monday, April 22, 2013 at 10:13am
-3 · -u · -7v + 8v - 6uv

## Answer This Question

## Related Questions

- Algebra 2 - -Explain the difference between log base b (mn) and ( log base b of ...
- Advanced Functions/ Precalculus Log - 1. Evaluate 4^(log base4 64) + 10^(log100...
- Precalc - 1. 1/3log base 8 of (x+1)=2log base 8 of 3-(2/3)log base 8 of (x+1) 2...
- math - Use the Laws of logarithms to rewrite the expression log(base 2)(11x(x-9...
- precalc - Solve: round to the thousandths if necessary! 1) 4^3/4x+5 = 12 2) log(...
- Trig - log base b 64 - log base b 16 = log base 4 16 solve for the variable.. i...
- Econ math/logarithms - If log with base b (2)=0.39 and log with base b (3)=0.61 ...
- Algebra - How can you find log base 3 of 242/5 using the given information ...
- check! - here is the question: log5(x-4)= log7x solve for x. These are just base...
- algebra - Find value of log (base 8)log (base 2) log (base 3)log (base 3) (27)^3...

More Related Questions